2011
DOI: 10.1111/j.2041-1626.2011.00092.x
|View full text |Cite
|
Sign up to set email alerts
|

Cystic variant of calcifying epithelial odontogenic tumor

Abstract: The calcifying epithelial odontogenic tumor is a rare benign odontogenic neoplasm of the jaw. Clinically, calcifying epithelial odontogenic tumor manifests as an intraosseous lesion (central type) in the majority of cases (95%). Extraosseous or peripheral lesions account for less than 5% of cases. Calcifying epithelial odontogenic tumor can be associated with an impacted tooth and give a radiographic simulation of dentigerous cyst. Most calcifying epithelial odontogenic tumors are solid in nature, histopatholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
21
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 14 publications
2
21
0
1
Order By: Relevance
“…Additionally, unlike the present case, over 50% of the cases are associated with an impacted tooth, 5,6 including 2 previously published cases of a cystic variant of CEOT. 1,2 Microscopically, the cystic variant of CEOT exhibits cystic lining ranging from focally thin nonkeratinizing stratified squamous epithelium to thickened epithelium with CEOT typical features, 1,2 similar to the current case. Recently, Urias Barrera et al 3 reported a clear cell cystic variant of CEOT.…”
supporting
confidence: 65%
See 3 more Smart Citations
“…Additionally, unlike the present case, over 50% of the cases are associated with an impacted tooth, 5,6 including 2 previously published cases of a cystic variant of CEOT. 1,2 Microscopically, the cystic variant of CEOT exhibits cystic lining ranging from focally thin nonkeratinizing stratified squamous epithelium to thickened epithelium with CEOT typical features, 1,2 similar to the current case. Recently, Urias Barrera et al 3 reported a clear cell cystic variant of CEOT.…”
supporting
confidence: 65%
“…Among the histological variants of CEOT, the true cystic variant of CEOT is extremely rare, with only 3 welldocumented cases reported in the English-language literature. [1][2][3] In this report, we describe the clinical, radiographic, and histopathological features of a case of cystic variant of CEOT.A 22-year-old male patient was referred to evaluation of a gingival swelling with approximately 8 months of evolution. Intraoral examination revealed a painless, dome-shaped, nodular lesion, which presented a bluish color and soft/cystic consistency to palpation.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Calcifying Odontogenic Cyst (COC). We can distinguish three entities: simple intra-osseous COC, extra-osseous peripheral COC and the malignant form Calcifying Cystic Odontogenic Tumor (CCOT) (21,23,(70)(71)(72)(79)(80)(81). COCs radiologically show a cystic imaging with small scattered areas of calcification, often resembling an odontoma (82).…”
Section: Orthokeratinized Odontogenic Cyst (Ooc)mentioning
confidence: 99%